HAKIKAT ADMINISTRASI PEMERINTAHAN ISLAM - Anzaikhan, M. (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
As a teaching that originates from revelation, Islam does not only speak in the orientation of aqidah and worship alone. More than that, Islam also discusses all scientific dimensions including good and efficient administrative models. The process of Islamization can take the form of a classical concept that is being tried again, or an offer for the future as a media solution in responding to the current government administration. A nation as large as the era of the Prophet Muhammad would not have survived if there were no solid and ideal government administration system. Likewise, in the time of the Bani Ummayah, the Abbasids, even the Ottoman era which carved the history of Islam as the largest and most respected group of its time. Once again, this glory could not have been achieved if the Islamic government at that time did not have the knowledge of qualified government administration. Administration is divided into two. (1) Administration in the strict sense is an administrative activity which includes the activities of note-taking, correspondence, bookkeeping and filing of letters as well as other matters intended to provide information and facilitate obtaining information back if needed. (2) Administration in the broad sense is the translation of the narrow meaning that includes the external function of the correspondence itself. Whether it is the background of the letter, the purpose of the letter, the benefits of the letter, the deadline of the letter, and so forth. On the scientific plane, administration has close significance with other scholars such as history, politics, social science, psychology, and even other applied sciences.